Diminished ovarian reserve in women with transfusion-dependent beta-thalassemia major: Is iron gonadotoxic?. (September 2017) - Uysal, Aysel; Alkan, Gül; Kurtoğlu, Ayşegül; Erol, Onur; Kurtoğlu, Erdal
Abstract: Objective: Iron accumulation in the endocrine glands has been implicated in the aetiopathogenesis of decreased reproductive capacity in patients with beta-thalassemia major (β-TM). The aim of the current study was to investigate the serum concentration of anti-Müllerian hormone (AMH), a marker of ovarian reserve, in women with transfusion-dependent β-TM. Study design: In this case-control study, we recruited 43 women with transfusion-dependent TM and 44 age-matched healthy controls. Hormonal and haematological parameters, serum level of AMH, antral follicle count, and ovarian volume were assessed. Results: Twenty-two of the 43 women were hypogonadotropic, 8 with primary amenorrhea and 14 with secondary amenorrhea. FSH, LH, estradiol, prolactin, and AMH levels; antral follicle count; and ovarian volume were significantly lower in women with TM compared with the control group (p < 0.05 for all). Conclusion: AMH level and other ovarian reserve markers are significantly diminished in women with transfusion-dependent TM compared to age-matched controls. Our findings support a deleterious effect of iron overload on ovarian tissue.